2021
DOI: 10.1007/s00256-021-03832-6
|View full text |Cite
|
Sign up to set email alerts
|

Patellar instability MRI measurements are associated with knee joint degeneration after reconstruction of the medial patellofemoral ligament

Abstract: Objective To qualitatively and quantitatively evaluate the 2-year magnetic resonance imaging (MRI) outcome after MPFL reconstruction at the knee and to assess MRI-based risk factors that predispose for inferior clinical and imaging outcomes. Materials and methods A total of 31 patients with MPFL reconstruction were included (22 ± 6 years, 10 female). MRI was performed preoperatively in 21/31 patients. Two-year follow-up MRI included quantitative cartilage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 73 publications
(101 reference statements)
0
10
0
1
Order By: Relevance
“…T1ρ relaxation times are more sensitive to concentration of proteoglycans, and T2 relaxation times are more sensitive to collagen structure. 15 Previous studies focused on general patellar instability, 8 multiple dislocations, 16,17 and surgical treatment for patellar dislocation 18 have shown elevated T2 relaxation times for cartilage on the patella. 18 A specific focus on the acute phase following a first-time patellar dislocation is lacking, but needed for longitudinal characterization of cartilage degradation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…T1ρ relaxation times are more sensitive to concentration of proteoglycans, and T2 relaxation times are more sensitive to collagen structure. 15 Previous studies focused on general patellar instability, 8 multiple dislocations, 16,17 and surgical treatment for patellar dislocation 18 have shown elevated T2 relaxation times for cartilage on the patella. 18 A specific focus on the acute phase following a first-time patellar dislocation is lacking, but needed for longitudinal characterization of cartilage degradation.…”
Section: Introductionmentioning
confidence: 99%
“…15 Previous studies focused on general patellar instability, 8 multiple dislocations, 16,17 and surgical treatment for patellar dislocation 18 have shown elevated T2 relaxation times for cartilage on the patella. 18 A specific focus on the acute phase following a first-time patellar dislocation is lacking, but needed for longitudinal characterization of cartilage degradation. Quantitative MRI-based evaluation of cartilage within the trochlear groove and tibiofemoral joint is also lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the patellar position remained lateral, and a lateral patellar position may lead to increased contact pressure to the lateral facet of the trochlea as previously described [ 9 ]. Giesler et al [ 46 ] reported that trochlear dysplasia parameters, TT-TG distance, and postoperative persistent high lateral patellar tilt were risk factors for progressive knee joint degeneration after MPFLR. This suggests that the remaining parameters of patellar instability could be affected for the progression of PFOA after patellar stabilization surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Although multiple MPFL reconstruction techniques have been described, the ideal surgical procedure for MPFL on the patellar side remains controversial [41], and the ideal stiffness after MPFL reconstruction remains unclear [51,52]. Although several studies have indicated that combined MPFL reconstruction with trochleoplasty can result in good postoperative stability and patient satisfaction [53,54], many concerns have been raised about the complication rate and the risk to the cartilage and progression of arthritis in the patellofemoral joint after this procedure [55,56].…”
Section: Discussionmentioning
confidence: 99%